2017
DOI: 10.3892/ijmm.2017.2907
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of policosanol enhances HDL functionality via CETP inhibition and reduces blood pressure and visceral fat in young and middle-aged subjects

Abstract: It is well-known that policosanol can improve serum lipid profiles, although the physiological mechanism is still unknown. Here, we investigated functional and structural changes in lipoproteins after consumption of policosanol. To investigate the physiological effect of policosanol, we analyzed serum parameters in young non-smoker (YN; n=7, 24.0±2.4 years), young smoker (YS; n=7, 26.3±1.5 years), and middle-aged subjects (MN; n=11, 52.5±9.8 years) who consumed policosanol daily (10 mg/day) for 8 weeks. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 44 publications
6
40
0
Order By: Relevance
“…There are a limited number of approaches to increasing HDL-C quantity comprising dietary foods or drugs to elevate the concentration of HDL-C and enhance HDL functionality (Sahebkar et al, 2016 ). Cuban policosanol (PCO) was reported to lower TC and low-density lipoprotein cholesterol (LDL-C) as well as increase HDL-C levels by inhibiting cholesterol synthesis and increasing LDL-C excretion (Janikula, 2002 ; Lee et al, 2016 ; Kim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are a limited number of approaches to increasing HDL-C quantity comprising dietary foods or drugs to elevate the concentration of HDL-C and enhance HDL functionality (Sahebkar et al, 2016 ). Cuban policosanol (PCO) was reported to lower TC and low-density lipoprotein cholesterol (LDL-C) as well as increase HDL-C levels by inhibiting cholesterol synthesis and increasing LDL-C excretion (Janikula, 2002 ; Lee et al, 2016 ; Kim et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Policosanol potentiates the beneficial functions of HDL as well as its antioxidant, anti-glycation, and anti-atherosclerotic activities (Lee et al, 2016 ; Kim et al, 2017 ). Although short-term consumption of policosanol has been shown to reduce brachial blood pressure (BP) accompanied by increased HDL-C concentration and antioxidative functionality, correlations of BP reduction with enhancement of HDL-C in TC remain to be investigated in a long-term study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,64 More recent double-blind placebo-controlled clinical trials have not shown any significant improvement in any measured lipids, including TC, LDL-C, TG, and HDL-C. A recent small study (14 subjects, underpowered) suggested that policosanol may improve HDL-C functionality, increase PON, lower glucose, reduce uric acid, decrease blood pressure and the oxidative stress marker malondialdehyde, and improve the lipid profile. 63 Other studies have found that policosanol may enhance the effects of statins and improve hepatic function. 66 Policosanol is not recommended at this time for the treatment of any form of dyslipidemia, pending more definitive studies with a larger study population.…”
Section: Policosanolmentioning
confidence: 98%
“…Policosanol is a sugar-cane extract of eight aliphatic alcohols that has undergone extensive clinical studies with variable results. 1,[63][64][65][66] Most of the earlier studies that showed positive results were performed in Cuba, and their validity has been questioned. 1,64 More recent double-blind placebo-controlled clinical trials have not shown any significant improvement in any measured lipids, including TC, LDL-C, TG, and HDL-C. A recent small study (14 subjects, underpowered) suggested that policosanol may improve HDL-C functionality, increase PON, lower glucose, reduce uric acid, decrease blood pressure and the oxidative stress marker malondialdehyde, and improve the lipid profile.…”
Section: Policosanolmentioning
confidence: 99%